Silicon and boron mitigate the effects of water deficit on sunflower - Jose M. G. Neves; Leonardo A. de Aquino; Paulo G. Berger; Júlio C. L. Neves; Genelício C. Rocha; Edimilson A. Barbosa (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the effect of Ca and Mg silicate and B on the gas exchange, leaf water potential and chlorophyll fluorescence parameters in the sunflower variety Embrapa 122 -V2000 under water stress conditions. The trial was conducted in Red Yellow Latosol with very clayey texture, with contrasting levels of Si and B and subjected to water deficit. The experimental design was randomized blocks in a 24 factorial arrangement, with five replicates. Treatments consisted of the combination of two acidity corrective agents (calcium magnesium silicate and dolomitic limestone), two levels of base saturation (30 and 70%), two levels of B (0.18 mg dm-3 - value available in the soil and 1.20 mg dm-3) and two water regimes (with and without water stress from the beginning of flowering). It can be concluded that the supply of Si and B can reduce the damage to sunflower caused by water stress.